Membangun Competitive Advantage GoPay: Peran Product Innovation dan E-Service Quality dengan Mediasi Customer Satisfaction - Timothy Marcellius Prathama; Gatot Nazir Ahmad; Terrylina Arvinta Monoarfa (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of Product Innovation, E-Service Quality, and Customer Satisfaction on Competitive Advantage at GoPay. This research uses a quantitative approach with survey techniques through online questionnaires, involving 112 respondents who are GoPay users in Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the aid of SmartPLS 4 software. The results show that Product Innovation has a significant positive effect on Customer Satisfaction, while E-Service Quality also has a significant positive impact on Customer Satisfaction. Furthermore, Customer Satisfaction was found to have a positive effect on Competitive Advantage. This study also reveals that Product Innovation and E-Service Quality indirectly affect Competitive Advantage through Customer Satisfaction as a mediating variable. The implications of this research emphasize the importance of product innovation and enhancing e-service quality to strengthen customer satisfaction and create a sustainable competitive advantage for GoPay in the face of competition in the fintech industry. These findings can serve as a reference for formulating more effective strategies to maintain GoPay's position in the increasingly competitive digital wallet market.